PENERAPAN MODEL TIPE STAD DALAM MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS VI SDS SOEKARNO HATTA - Rahmat Subekti; Mastur; Siti Patimah; M. Makhrus Ali; Latief Arung Arafah (Program Studi Manajemen Pendidikan Islam, 2024)
This research was motivated by the lack of active learning of students in Islamic Religious Education subjects especially on Asmaul Husna material and the teacher has not found a learning method or model that is appropriate to the Asmaul Husna material in increasing students' learning activeness. The formulation of this problem is: Can the application of the STAD type cooperative learning model increase learning activity in Islamic Religion subjects for Class VI students? The subjects in this research were 20 class VI students. Meanwhile, the aim of this research is the application of the STAD type cooperative learning model to increase student learning activity in Islamic Religion subjects for Class VI students. The STAD type cooperative learning model is a learning model carried out by actively implementing students in learning through observing, asking questions, discussing and presenting the results of the discussion. The author uses this learning model in Islamic Religious Education subjects